Dynamics of Antibiotic Prescription in Royal Hampshire County Hospital in November 2016: A Prospective Study - Lee-A-Ping, Kathrine; Saeed, Kordo; Dryden, Matthew; Sim, Gavin (International Journal of Medical Students, 2017)
Background: Antimicrobial Stewardship and The Start Smart – Then Focus strategy provide guidelines aimed at improving the increasing trend of antibiotic resistance. The aim of this study was to assess whether antibiotics were being prescribed at Royal Hampshire County Hospital (a district general hospital), in accordance with the hospital’s and the NICE guidelines and whether this followed the Start Smart – Then Focus approach. Methods: During November 2016, medical notes of 12 randomly selected in-patients of Royal Hampshire County Hospital on 45 antibiotics, were used to measure the dynamics of their prescriptions. Results: 91% of the 45 prescriptions were in accordance with hospital guidelines, 82% of cases had appropriate samples sent before commencing antibiotics, 5% out of 27% had a planned switch from intravenous administration to oral (the remaining 73% were initially started on oral regimes) and 80% had planned stop dates. Conclusion: Appropriate samples, stop dates, planning and documentation in patient notes must be improved with regards to antibiotic use.